(untitled) (Global Journal of Science Frontier Research, 2025)
In this paper, we discuss the existence of a monotonic positive solution for the following fourth-order three points Non-linear BVP: which has the sign -changing Green’s function. where and . The point is that although the corresponding Green is changing the sign, by applying iterative methods, We can still obtain the existence of a monotonic positive solution under certain suitable conditions of .